Analisis Mengenai Unsur Pelayanan Publik Di Dalam Peraturan Gubernur Bali Nomor 46 Tahun 2020 Tentang Penerapan Disiplin Dan Penegakan Hukum Protokol Kesehatan Sebagai Upaya Pencegahan Dan Pengendalian Covid-19 - Desak Komang Budiarsini; Putu Dita; Agus Ary Wahyudi (Jurnal Locus Delicti, 2020)
The writing of this article aims to find out and analyze how the analysis of Governor Regulation Number 46 of 2020 concerning the Application of Discipline and Law Enforcement of Health Protocols as Efforts to Prevent and Control Covid-19 seen from the rapid spread of the corona virus at this time. After the announcement of a positive case for the Covid-19 virus by the government on March 2 (two) 2020, the government continued to increase efforts and policies to suppress transmission of this virus. Starting from limiting social relationships (social distancing), limiting physical contact relationships (physical comparison) by appealing to all State apparatus, BUMN employees and private employees to limit activities in the office by encouraging work from home. The writing of this article is a research that uses a normative research method, using a statutory approach. Then analyzed descriptively qualitatively using primary, secondary, and tertiary legal materials to get conclusions that are relevant to the problems at hand. The result of writing this article is how the form of public services provided by the Bali provincial government to the community to deal with or prevent the spread of Covid-19.